Effects of rumen-escape lipid in a range supplement on postpartum reproductive function in beef cows - Hightshoe, R.B.; Cochran, R.C.; Corah, L.R.; Harmon, D.L.; Kiracofe, G.H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Postpartum cows receiving a range supplement containing rumen-escape lipid exhibited altered hormone and cholesterol levels compared to cows not fed lipid. Sixty-seven percent of lipid-fed cows exhibited a normal (18.2 d) first estrous cycle vs 33% for cows not receiving lipid. Incorporation of rumen-escape lipid into range supplements appears to significantly improve postpartum reproductive characteristics.
Keywords: Beef; Rumen-escape lipid; Estrous cycle; Cholesterol; Postpartum